Analisis Kekuatan Pondasi Tangki Fame Biodiesel pada Proyek PT. X di Gresik - Irawan Agustiar; Ikhtisholiyah; Subali (Wahana Teknik, 2021)
In the current era of globalization, many countries are competing to open themselves as wide as possible, so that investors can be interested in investing. It is an extraordinary gift in this country, where oil palm plants thrive on the islands of Sumatra, Kalimantan, Sulawesi to Papua, which can be a renewable energy power today and in the future. Where energy from fossil fuels will one day run out, while biodiesel can still exist by cultivating oil palm plants continuously. This is truly an extraordinary breakthrough for all nations in the world, because this energy can be renewed. Ease of bureaucracy is created so that investors continue to develop and build factories that process derivatives from vegetable oil, into fuel oil known as fame (fatty acid methyl ester) biodiesel. The increasing demand for fame in the national and international markets has prompted the company to establish processing plants and tanks as a place to store fame liquid. The Fame Biodiesel Tank is a temporary storage place for liquid oil or bulk oil for companies before being distributed to gas stations or to end users. The importance of this storage tank is to store daily products so that the tank capacity is made quite large 5000 kL, this requires an analysis of the strength of the foundation so that the tank is safe when in use. In the discussion of the design, the calculated loads are dead load 5,957.57 kg/m2, live load 22,555.22 kg/m2, wind load 240,249.24 kg/m, earthquake overtuning moment 8,207,090 kg.m, and combined loads. This data was then analyzed using the standard SNI-1726-2012 and API 650 (American Petrolium Institute) followed by analysis using the Staad Pro Advanced software, the design strength of the pile bearing capacity was 95 ton/point, using a concrete plate thickness of 60 cm thick, with iron BJTD reinforcement with a diameter of 16 mm with an axle spacing of 150 mm. Application of standards SNI-1726-2012 and API 650 (American Petrolium Institute) and calculations using Staad Pro Advanced software, so that calculations are faster and more accurate so that the construction of tank buildings built on foundations using pile foundations is really strong and can withstand load of the oil liquid to the maximum according to its capacity. It was concluded in this study that with a tank diameter of 19.26 meters and a height of 22.5 meters, the maximum moment Mx = 2.998 MT.m, My = 189.171 MT.m, pile bearing capacity 95 ton/point, 85 points @ 22 meters. In the process of changing the liquid product in the tank from fame biodiesel liquid (density 0.88) to crude palm kernel oil (density 0.9156), or with refined bleached deodorized palm kernel oil (density 0.9160), the condition the tank is still safe and the fluid can be replaced. Keywords: analysis, biodiesel, foundation, pile, staad pro, spun, tank.